A Novel Approach for RFID Based Object Detection and Locating System - Ankali, Sanjay B.; Pharalad, Ashwini; Akiwate, Bahubali; Gollagi, S.G. (International Journal of Scientific Research in Computer Science and Engineering, 2022)
It is the human tendency to mess up with finding the miss placed day-to-day objects such as car keys, spectacles, mobile chargers, etc. A survey shows that nearly 68% of working people find it difficult to find these necessary objects. This causes unnecessary wastage of time especially during getting ready for office. In this paper, we propose a low-cost RF-based object-locating system that uses compact RF-based object locators that can be attached to daily-use objects such as keys, spectacles, and chargers. The android-based application is developed to track the proximity of such RF trackers using BLE protocol. The application detects the signal strength to check the proximity of the target object. The proposed methodology uses both one-way and two-way trackers to provide proximity as well as proximity with a remote alarming system respectively to trigger an alarm for easy finding of the object from the developed android application. The proposed system can help in tracking and locating the objects using low energy and efficient Bluetooth transmission protocol. The system also implements GPS-based tracking of the objects on the map which can give the exact geographical coordinates along with the objects` position on the map. w.r.t. to the android application. The results show that the system works with 100% and 92% for indoor and GPS tracking respectively.